2015
DOI: 10.1111/head.12613
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation, Cranial Autonomic Symptoms, and Functional Disability in Migraine: A Questionnaire‐Based Study in Tertiary Care

Abstract: Patients who reported seasonal variation in migraine also reported more CASs and had more severe functional disability. The profound functional disability in the migraineurs reporting seasonal variation or CAS also provides direction for proactive clinical management in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Another common feature of allergic rhinitis and migraine is their seasonal exacerbation in the spring, fall, and summer months as a result of allergic triggers [ 35 •, 39 , 48 , 49 ]. A study from South Korea conducted between 2005 and 2013 showed that 13.5 % of migraine patients reported seasonal exacerbations [ 48 ].…”
Section: Why Sinus Headache Is a Diagnostic Challenge: Similarities Amentioning
confidence: 99%
See 1 more Smart Citation
“…Another common feature of allergic rhinitis and migraine is their seasonal exacerbation in the spring, fall, and summer months as a result of allergic triggers [ 35 •, 39 , 48 , 49 ]. A study from South Korea conducted between 2005 and 2013 showed that 13.5 % of migraine patients reported seasonal exacerbations [ 48 ].…”
Section: Why Sinus Headache Is a Diagnostic Challenge: Similarities Amentioning
confidence: 99%
“…Another common feature of allergic rhinitis and migraine is their seasonal exacerbation in the spring, fall, and summer months as a result of allergic triggers [ 35 •, 39 , 48 , 49 ]. A study from South Korea conducted between 2005 and 2013 showed that 13.5 % of migraine patients reported seasonal exacerbations [ 48 ]. Moreover, the costs of migraine treatment are higher during allergy season [ 49 ], because many people with migraine experience an increase in headache intensity and frequency due to coexisting allergic rhinitis [ 50 ].…”
Section: Why Sinus Headache Is a Diagnostic Challenge: Similarities Amentioning
confidence: 99%
“…Furthermore, attenuation of the pupillary light reflex, as documented both in the wake of migraine attacks and in the interictal phase of cluster headache has been suggested as a hypothalamic compensatory mechanism due to increased locus coeruleus‐activity. In view of that, SM may represent a state with increased hypothalamic dysfunction as reflected in the Korean study where they found increased cranial autonomic symptoms (CAS) in patients who reported seasonal variation . Unfortunately, the frequency of CAS in the present cross‐sectional was not evaluated.…”
Section: Discussionmentioning
confidence: 79%
“…The present survey is not optimally designed to give the answers, but patients in our clinical practice have reported less severe headache when using preventive treatment only in the polar day season . Subsequently, 769 Korean migraineurs without aura reported SM in 104 (13.5%) of the participants . These patients had more cranial autonomic symptoms, photophobia, phonophobia, neck pain, and intolerance to physical activity, weekend migraine, and functional disability than others …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation